The effect of kinesiophobia on gastrointestinal disorders in patients with lower extremity orthopedic surgery - Gunes, Huseyin; Bulbuloglu, Semra; Saritas, Serdar; Ozdemir, Ahmet (Frontiers in Surgery, 2025)
BackgroundPostoperative kinesiophobia and gastrointestinal (GI) disorders are common and undesirable conditions following orthopedic surgery. Additionally, managing both conditions is crucial for preventing complications and accelerating recovery. The purpose of this study is to investigate the effects of kinesiophobia on GI disorders after lower extremity orthopedic surgery.MethodThis study was conducted with a descriptive and cross-sectional design. The sample consisted of a total of n = 299 patients who underwent orthopedic surgery in their lower extremities at the orthopedics and traumatology clinic of a research and training hospital located in Turkey. A personal information form, the Tampa Scale of Kinesiophobia (TSK), and the Gastrointestinal Symptom Rating Scale (GSRS) were used to collect data, and the obtained data were analyzed using descriptive statistics, one-way analysis of variance (ANOVA), paired-samples t-test, and post hoc tests when necessary.ResultsWhile 24.4% of the patients were aged 65–74 years, 51.5% were male. The mean total TSK score of the patients was above average (49.36 ± 8.74), while their mean total GSRS score was below average (31.22 ± 11.7). In our study, as kinesiophobia increased, the frequency of bowel movements decreased, and kinesiophobia explained 19.9% of the variance in GI disorders (p < 0.05).ConclusionsKinesiophobia is a significant predictor of GI disorders in patients who underwent lower extremity surgery. Returning to normal GI function after surgery is crucial for preventing complications in patients with lower extremity surgery. Uncontrolled kinesiophobia after surgery exacerbates GI disorders. Therefore, early diagnosis and management of both kinesiophobia and GI disorders are necessary for rapid recovery in patients with lower extremity surgery.